The impact of circWWC3 on neoadjuvant therapy for triple-negative breast cancer and the construction of a nomogram for predicting pathological complete response after neoadjuvant therapy - Wang, Haoqi; Liu, Hongbo; Gao, Shan; Wang, Lijia; Bai, Zihao; Zhang, Yi; Zhang, Peijin; Liu, Fei; Geng, Cuizhi (Frontiers in Oncology, 2025)
BackgroundThe introduction of novel strategies for neoadjuvant therapy (NAT) has significantly enhanced the rate of pathological complete response (pCR) in patients with triple-negative breast cancer (TNBC). However, due to tumor heterogeneity, some patients continue to experience poor treatment efficacy, early recurrence, metastasis, and even mortality. Therefore, it is crucial to identify new molecular targets for precise treatment and to develop predictive models for pCR to facilitate tailored therapeutic approaches.MethodsWe conducted a study involving a cohort of TNBC patients who underwent NAT, collecting data on clinicopathological indicators, MRI parameters, and pathological remission outcomes. The expression levels of baseline circular RNA WWC3 (circWWC3) in breast cancer tissue were assessed, and the relationship between its expression and clinicopathological indicators as well as pathological response was analyzed. A nomogram for predicting pCR in TNBC was developed and subsequently validated.ResultsFrom January 2020 to December 2023, a total of 205 patients were included in the final analysis. The rate of total pathological complete response (tpCR), defined as ypT0/is and ypN0, was observed to be 51.7%. CircWWC3 was found to be highly expressed in the cytoplasm, with an expression rate of 79% among all analyzed cancerous tissues. The elevated expression of circWWC3 was positively correlated with T2 stage, N1 status, Ki-67 levels greater than 30%, and moderate to high infiltration of tumor-infiltrating lymphocytes (TILs) (p < 0.05). Additionally, a change rate in the apparent diffusion coefficient (ADC) of breast MRI after two cycles of neoadjuvant therapy (ΔADC 0-2%) greater than 24.53% was significantly associated (p < 0.05). Patients exhibiting high levels of circWWC3 expression were more likely to achieve pCR. Univariate and multivariate regression analyses identified TILs, ΔADC 0-2%, and circWWC3 as key variables for constructing a predictive nomogram for pCR. This model demonstrated strong discrimination, calibration, and clinical applicability.ConclusionElevated expression levels of circWWC3 serve as an independent risk factor influencing the likelihood of achieving a pCR. A predictive model that integrates circWWC3 expression alongside pathological and imaging parameters demonstrates a robust capacity to accurately forecast the probability of pCR in patients diagnosed with TNBC.